Common Contractual Behaviour of Key Participants in Civil Engineering Projects - Wan Ismail, Wan Norizan; Adnan, Hamimah; Ismail, Noor Akmal Adillah (International Journal of Sustainable Construction Engineering and Technology, 2021)
The delivery of civil engineering projects in Malaysia largely has been beset by cost overrun, schedule delays, shoddy workmanship. Previous studies have replete that most of the problems which hinder the project success are related to the unfavourable contractual behaviour of the project key participants who do not adhere to and comply with the terms of the contract in project implementation. Hence, the purpose of this paper is to investigate the factors that hindered the success of civil engineering projects focusing on the aspect of contractual behavior of key participants. The objective of this study is to determine the common contractual behavior of key participants in civil engineering projects in Malaysia. The data of this study was obtained from professional civil engineer registered with Board of Engineers Malaysia (BEM) and Grade G7 contractors registered with the Construction Industry Development Board (CIDB) via a questionnaire survey. Based on the result from 288 questionnaire survey, this study highlighted five (5) contractual behaviour of key participants which all this while hindered the civil engineering project success. They were the delay of interim payment, delay of contractor’s work progress, delay of issuing project information, ineffective communication between engineer and contractor and unauthorised instructions. The severity of contractual behaviors’ occurrence is important to be empirically researched to understand the contractual root causes that largely affect project performance and eventually can comprehensively be placed more concerned for improvement for future projects.